Sphenomandibular ligament calcification causing progressive restriction of mouth opening: case report and literature review. (22nd September 2013) - Salha, R.; Shah, J.; Sidebottom, A.J.
Abstract A 46‐year old male presented with a 3‐year history of restricted mouth opening following inferior alveolar block injections for dental treatment. An initial magnetic resonance imaging and subsequent three‐dimensional computed tomography scans reported the cause as lateral pterygoid calcification and temporalis muscle calcification, respectively. Physiotherapy was initially helpful but relapse occurred. Intraoperatively coronoidectomy was unsuccessful, and it was discovered that he had fibrosis and calcification of the sphenomandibular ligament. Release of this band improved his opening, and this has been maintained for 1 year.